Frequently Asked Questions on Model RFQ Document - Planning Commission (Planning Commission, 2009)
The increasing demand for infrastructure within the country, coupled with limited resources, has persuaded the government to explore alternative means of financing infrastructure projects. In the quest for finding such resources, a credible alternative has been found in Public Private Partnerships(PPPs) which ensure that the obligation to provide the services remains with the government albeit the means of delivery are private entities. In the process, efficiencies of the private sector are harnessed at competitive costs, thereby benefiting both the user and the government, apart from attracting private capital to fund public projects. This, however, is predicated on a policy and regulatory framework that provides a fair, transparent and competitive environment as flaw's in the framework can lead to unintended outcomes. Cautious and diligent approach is, therefore, necessary while formulating the rules of engagement. The success of a PPP project is vastly dependent on the criteria for selection of the concessionaire, especially as these projects typically involve large capital investments for providing essential infrastructure services to users on a long-term basis.
Planning Commission Government of India
Planning Commission Government of India